Identifying Invaders: The Case of Ceratium furcoides (Gonyaulacales, Dinophyceae) in South America - Accattatis, Victoria (2020)
Ceratium furcoides is an invasive freshwater dinoflagellate that in the last three decades has expanded its geographic distribution in South America, being recently found in Paraná River floodplain (Argentina). Despite growing concern about the presence and impacts of this invader, information regarding genetic diversity in the Southern Hemisphere is missing. This work constitutes the first phylogenetic characterization of Ceratium populations of South America, particularly, from the Paraná system. After taxonomic identification as C. furcoides based on morphological traits, two sequencing-based approaches were applied using the ribosomal 18S gene: Sanger sequencing to isolated individuals and high-throughput amplicon sequencing (HTS) to environmental DNA. The sequence of C. furcoides obtained shared 100% identity to Asian sequences, and formed a highly supported clade in the constructed reference phylogenetic tree. HTS helped to recover low-frequency genetic variants suggesting the presence of different population of C. furcoides, and to alert potential invasion in its early stages.